Constrained multi-objective optimization of radial expanders in organic Rankine cycles by firefly algorithm - Bahadormanesh, Nikrouz; Rahat, Shayan; Yarali, Milad (Energy conversion and management, 2017)
•A multi-objective optimization for radial expander in Organic Rankine Cycles is implemented.•By using firefly algorithm, Pareto front based on the size of turbine and thermal efficiency is produced.•Tension and vibration constrains have a significant effect on optimum design points. Organic Rankine Cycles are viable energy conversion systems in sustainable energy systems due to their compatibility with low-temperature heat sources. In the present study, one dimensional model of radial expanders in conjunction with a thermodynamic model of organic Rankine cycles is prepared. After verification, by defining thermal efficiency of the cycle and size parameter of a radial turbine as the objective functions, a multi-objective optimization was conducted regarding tension and vibration constraints for 4 different organic working fluids (R22, R245fa, R236fa and N-Pentane). In addition to mass flow rate, evaporator temperature, maximum pressure of cycle and turbo-machinery design parameters are selected as the decision variables. Regarding Pareto fronts, by a little increase in size of radial expanders, it is feasible to reach high efficiency. Moreover, by assessing the distribution of decision variables, the variables that play a major role in trending between the objective functions are found. Effects of mechanical and vibration constrains on optimum decision variables are investigated. The results of optimization can be considered as an initial values for design of radial turbines for Organic Rankine Cycles.